PROSES PEMBUATAN DAN ANALISIS STATIC PADA HORZ CAM MASEMA AW6035-SR MENGGUNAKAN SOFTWARE SOLIDWORKS 2019 DI PT. WOTOSINDO METAL PRATAMA - Abdul Rahman Agung Ramadhan; Eko Aprianto Nugroho (Asosiasi Dosen Muda Indonesia, 2023)
In this modern era, the industrial world continues to experience rapid development, especially in the manufacturing process, particularly in machining processes. The production process is a way, method, and technique for creating, processing, or adding value to a product or service using available resources such as labor, machinery, materials, and funds. The purpose of this writing is to understand the production process for making Horz Cam Masema AW6035- SR using VCN 150 material. It also involves simulating static tests using Solidworks software to analyze von misses, displacement, and fatigue values. This writing is based on field studies and literature reviews conducted by the author. The simulation results conducted with a torque loading of 16.67 Nm obtained a maximum von misses value of 228,788,416 N/m2 and a displacement value of 0.222 mm. Therefore, the obtained fatigue values include the highest damage percentage of 0.488 and a minimum total life of 204,845 times.